An Analysis of Transportation Mode Choice in Bitung City Using Structural Equation Modeling - Lefrandt, Lucia Ingrid Regina; Punuhsingon, Charles S. C. (The Islamic Education and Multiculturalism Foundation, 2024)
Transportation is the foundation of daily life and is vital to a region's economic and social development. Transportation is a crucial aspect of human life, facilitating connections between locations. Mode choice is a critical consideration in transportation planning, influenced by cost, travel time, and comfort factors. This study aims to analyze the characteristics of travelers in Bitung City Regency and the factors influencing their choice of transportation modes in 2024. The research involved distributing an online questionnaire to 200 respondents and gathering data on various latent variables, including Travel Cost, Travel Time, Vehicle Condition, and Comfort Level. The analysis used Structural Equation Modeling (SEM) with SPSS and AMOS software. The study revealed a significant gender disparity among the respondents, with men dominating the demographics at 60%. Most respondents were from the 26–35-year age group (40%), had a private status (35%), and had completed high school or vocational school (35%). Motorbikes were the most common regarding vehicle ownership, with 60% of respondents owning one. The SEM analysis revealed significant factors influencing transportation mode choice. Travel Time (WT) had a negative effect on Comfort Level (TK) and Vehicle Condition (KK), with t-values of -0.684 and -0.895, respectively, indicating that longer travel times reduce comfort and vehicle satisfaction. Vehicle Condition (KK) significantly influenced the preference for Online Transport (TO) and Conventional Ojek (OK) with t-values of 0.597 and 0.278, respectively. Comfort Level (TK) significantly impacted the preference for Public Transport (TU), Conventional Ojek (OK), and Online Transport (TO) with t-values of 0.728, 0.530, and 0.301, respectively. The findings of this research have practical implications, suggesting that enhancing travel time efficiency, vehicle conditions, and overall comfort can significantly influence mode choice preferences. These insights can engage and interest transportation planners, policymakers, and researchers, guiding future transportation planning and policymaking in Bitung City Regency.